Orientation of rusty grain beetles, Cryptolestes ferrugineus (Coleoptera: Laemophloeidae), to semiochemicals in field and laboratory experiments. (December 2019) - Losey, Stephen M.; Daglish, Gregory J.; Phillips, Thomas W.
Abstract: Cryptolestes ferrugineus is a common beetle pest of stored grain for which techniques to monitor dispersing beetles are limited. Early research found several male-produced aggregation pheromones, but there has been little related work since that time. This paper reports experiments on orientation of C. ferrugineus in response to synthetic pheromones and other semiochemicals via flight and walking. Field trapping studies showed that flying beetles were caught on the western sides of grain bins in Kansas compared to the other three cardinal directions. Work with synthetic formulations of the two male-produced aggregation pheromones found that flying beetles were attracted to traps with the pheromone and wheat compared to traps with wheat only. Walking bioassays in the laboratory determined that either of the two aggregation pheromones, known as Cucujolide I and Cucujolide II, were attractive whether deployed singly or in combination. Laboratory bioassays showed that volatiles from grains, other grain-based materials and two commercial food attractants used in traps were attractive to C. ferrugineus . Further laboratory assays demonstrated that C. ferrugineus would orient to synthetic pheromones of three other beetle species and one moth species, all common pests of stored products. These new data on semiochemicals for C. ferrugineus suggest future work that could be done toward developing new tools for detecting and monitoring this serious pest. Highlights: Cryptolestes ferrgineus were trapped flying near the western sides of grain bins. Traps with synthetic pheromone caught more beetles than traps without pheromone. Beetles were attracted in the lab to their pheromones, food odors, and pheromones of other species. This work suggests that trapping methods with semiochemicals could be developed for this pest.